(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Cetirizine as general OTC anti-allergic drug was evaluated through paper chromatography. Twelve cetirizine compositions were analysed wherein each tablet and syrups were six in number. Seven solvent systems were experimented from which chloroform and methanol in ratio 50:50 proved to be best solvent system for both cetirizine tablet and syrup compositions. Other solvent system that showed clear separation of spots were n-hexane, toluene and diethyl ether in ratio 65:25:10 and acetone and methanol in ratio 90:10 for tablet and syrup preparations respectively. Iodine fuming technique and UV radiations were also utilized for visualising some unidentified and invisible spots during the examination procedures.